POST-OPERATIVE COMPLICATION’S OF DUCKETT’S URETHROPLASTY IN ANTERIOR HYPOSPADIAS WITH CHORDEE - Ijaz ur Rehman (Gomal Journal of Medical Sciences, 2017)
Background: Hypospadias is a common congenital urological problem with the incidence of one in three hundred male children. It is usually associated with chordee. Generally hypospadias with chordee is managed in two stages. In this we studied post-operative complications of Duckett’s urethroplasty with chordee for hypospadias, to have a scientific proof that it is a safe, economical and easy procedure. Material & Methods: This descriptive study was conducted at Department of Urology Lahore General Hospital Lahore affiliated with Postgraduate Medical Institute Lahore from 1st January 2015 to 31December 2015 during which Duckett’s urethroplasty was done for 42 male children with hypospadias with chordee. Post-operative complications were observed in these children till 6 months of their post-operative period. Data entry and analysis was done by using SPSS 17. Results: Mean age of patients was 6.28 years, with range of 2-12 years. None of the patients was found to have operative site infection or totally disrupted tube till they were followed up for a period of 6 months. Whereas at 1st month of follow-up 4.76 % of the patients had Urethrocutaneous fistula. Meatal stenosis was found in 4.76% of the patients at 3rd month of their follow-up. Conclusion: Duckett’s technique has good post-operative results. It can be opted for patients of hypospadias with chordee as a single staged procedure when combined with urethroplasty.